A 7 series high-strength corrosion-resistant aluminum alloy and preparation method thereof

By optimizing the composition and process in the 7-Series aluminum alloy, including ultrasonic treatment and heat treatment, high-strength and high corrosion resistance aluminum alloys are prepared, which solves the problem of imbalance in the strength and corrosion resistance in the existing technology, and meets the current situation application requirements in the field.

CN116694968BActive Publication Date: 2024-12-17GUANGYA ALUMINUM +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310421511.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-19
Publication Date
2024-12-17
Estimated Expiration
2043-04-19

AI Technical Summary

Technical Problem

The existing 7-Series aluminum alloys are difficult to balance between high strength and corrosion resistance, and cannot meet the current field's demand for high strength and corrosion resistance.

Method used

A 7-type high-strength corrosion-resistant aluminum alloy with specific components is used, including Zn6.1% to 6.4%, Mg1.5% to 1.7%, Cu0.25% to 0.35%, Fe≤0.15%, Si≤0.04%, and Ti0.03 The composition of % to 0.08%, through ultrasonic treatment, online grain refinement, degassing filtration, semi-continuous casting, extrusion forming and heat treatment, combined with surface phosphating and silanization treatment, the tensile strength is greater than 580MPa and yield Aluminum alloy with a strength greater than 550MPa and a corrosion resistance grade of no lower than PA grade.

Benefits of technology

The high strength and corrosion resistance of aluminum alloy are balanced, the high strength and corrosion resistance are met, and the reliability of use is ensured in harsh environments such as the ocean.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004186997680000151
    Figure BDA0004186997680000151
  • Figure BDA0004186997680000161
    Figure BDA0004186997680000161
Patent Text Reader

Abstract

The invention discloses a 7 series high-strength corrosion-resistant aluminum alloy, and obtains a 7 series aluminum alloy with fine grains, high strength and good corrosion resistance through refining, ultrasonic treatment, refinement treatment, degassing filtration, ingot casting and aging treatment, wherein the strength is not lower than the strength obtained by the peak aging process; when the alloy is melted and cast, the ultrasonic casting technology is adopted to perform ultrasonic treatment on the melt, and the "cavitation effect" is used to increase the nucleation of grains and break the grains, thereby realizing grain refinement and improving the comprehensive mechanical properties of the alloy; through an extrusion process and a heat treatment process, a discontinuous coarse η phase is generated at the grain boundary through a regression and re-aging process, so as to delay the occurrence of corrosion along the grain boundary and improve the corrosion resistance of the alloy; the tensile strength of the 7 series high-strength corrosion-resistant aluminum alloy is greater than 580MPa, the yield strength is greater than 550MPa, the elongation is greater than 14%, the exfoliation corrosion resistance grade is not lower than the PA grade, the strength and corrosion resistance are balanced, and the demand for high strength and strong corrosion resistance in the current field can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of aluminum alloy manufacturing, and in particular to a 7 series high-strength corrosion-resistant aluminum alloy and a preparation method thereof. Background Art

[0002] With the acceleration of lightweighting process, the application of aluminum alloys in aircraft, automobiles, ships, rail transportation and other fields has gradually increased. These fields have higher and higher requirements for the comprehensive performance of aluminum alloys, especially in the use of some structural parts, which require aluminum alloys to have higher strength and better corrosion resistance to adapt to the environment of ocean, acid rain weather and other environments to ensure the safety of transportation.

[0003] As a heat-treatable and strengthened aluminum alloy, the 7 series aluminum alloy has the advantages of good hot processing performance, high strength, and good welding performance, and is widely used in the above-mentioned fields. However, this type of alloy often has the characteristics of poor corrosion resistance, which limits its application scenarios. In the existing technology, the idea to solve this problem is often to use special heat treatment methods to improve its corrosion resistance at the expense of reducing the strength of the alloy, and its final strength is often lower than the strength of conventional peak aging. Among them, "peak aging" refers to the aging process system corresponding to the highest strength obtained by heat-treatable and strengthened aluminum alloys through single-stage aging.

[0004] To sum up, after massive searches by the applicant, there is at least an imbalance between the strength and corrosion resistance of the prepared aluminum alloy in this field, especially the problem that the strength cannot meet the needs of the current field. Therefore, it is necessary to develop or improve a 7 series high-strength corrosion-resistant aluminum alloy and a preparation method thereof, so that it can obtain high corrosion resistance while having a high strength not lower than that obtained by the peak aging process, so as to meet the application needs of aluminum alloys in different fields. Summary of the invention

[0005] Based on this, in order to solve the problem that the strength and corrosion resistance of the prepared aluminum alloy are unbalanced, especially the problem that the strength cannot meet the current field requirements, the present invention provides a 7 series high-strength corrosion-resistant aluminum alloy and a preparation method thereof. The specific technical scheme is as follows:

[0006] A 7 series high-strength corrosion-resistant aluminum alloy comprises the following components in percentage by mass: 6.1% to 6.4% Zn, 1.5% to 1.7% Mg, 0.25% to 0.35% Cu, ≤0.15% Fe, ≤0.04% Si, 0.03% to 0.08% Ti, and the balance being Al.

[0007] Furthermore, other impurities are included, and the total amount of the other impurities is ≤0.15%.

[0008] Furthermore, the 7 series high-strength corrosion-resistant aluminum alloy has a tensile strength greater than 580 MPa, a yield strength greater than 550 MPa, an elongation greater than 14%, and an exfoliation corrosion resistance grade not lower than PA grade.

[0009] The technical solution also provides a method for preparing a 7-series high-strength and corrosion-resistant aluminum alloy, comprising the following steps: Step 1: selecting Al-20Cu alloy, Al-5Ti-B alloy wire, aluminum ingots with a purity of 99.8%, zinc ingots with a purity of 99.9%, and magnesium ingots with a purity of 99.9% as raw materials;

[0010] Step 2: heating the aluminum ingot to melt at 730°C to 750°C, then adding 6.1% to 6.4% of zinc ingot, 1.5% to 1.7% of magnesium ingot, and 1.25% to 1.75% of Al-20Cu alloy accounting for the total weight of the raw materials, stirring and melting to form an aluminum alloy melt;

[0011] Step 3: Use sodium-free refining agent and argon gas to spray refine the aluminum alloy melt at a refining temperature of 730℃~750℃, and refine it multiple times. Each refining time is 25min~40min. After refining, slag is removed and then left to stand for 25min~35min.

[0012] Step 4: Use ultrasonic metal melt treatment equipment to ultrasonically treat the aluminum alloy melt, with a power of 150W to 200W and a vibration time of 5min to 10min;

[0013] Step 5: The aluminum alloy melt in the furnace is introduced into the flow channel, and the Al-5Ti-B alloy wire is added into the aluminum alloy melt for online grain refinement treatment;

[0014] Step 6: The aluminum alloy melt is sequentially passed through a degassing box with a rotation speed of 200 to 300 rpm and an argon flow rate of 4 to 5 cubic meters per hour and a double-layer foam ceramic filter plate with a porosity of 40ppi+60ppi, for online degassing and filtration treatment;

[0015] Step 7: semi-continuously casting the aluminum alloy melt into an aluminum alloy ingot under the conditions of a casting temperature of 710°C to 740°C, a casting speed of 90mm / min to 100mm / min, and a cooling water pressure of 0.1Mpa to 0.2Mpa;

[0016] Step 8: Heat the aluminum alloy ingot to 450°C to 490°C for homogenization treatment for 20 hours to 28 hours, and then force cool it to room temperature with water mist;

[0017] Step 9: heating the aluminum alloy ingot after homogenization treatment to 450°C to 470°C, extruding it at an extrusion speed of 8m / min to 12m / min to obtain an extruded aluminum alloy, and then cooling it to room temperature through water;

[0018] Step 10: Heat the extruded aluminum alloy to 110℃~130℃ and age for 22 hours to 26 hours, then quickly heat to 185℃-210℃ and keep warm for 15min-25min, quickly water cool to room temperature and continue to heat to 110℃~130℃ and age for 22 hours to 26 hours.

[0019] Furthermore, in the third step, the amount of sodium-free refining agent added is calculated based on 3 kg of refining agent per ton of aluminum alloy melt.

[0020] Furthermore, in the fifth step, the Al-5Ti-B alloy wire is added online at a rate of 0.004% to 0.01% of the total raw material addition amount, and the adding speed is 2m / min to 3m / min.

[0021] Furthermore, in the ninth step, the extrusion die temperature is 440°C-460°C, the extrusion barrel temperature is 400°C-420°C, and the outlet temperature is 490°C-510°C.

[0022] Furthermore, the preparation method of the 7 series high-strength corrosion-resistant aluminum alloy further comprises the following steps:

[0023] Step 11: Surface phosphating treatment; cool the extruded aluminum alloy that has completed the aging treatment in step 10 to 60°C-80°C, degrease the surface of the extruded aluminum alloy after cooling, and wash and dry it with deionized water after degreasing; preheat the extruded aluminum alloy to 70°C-80°C; spray the phosphating solution for the first time after preheating; air dry for the first time after the first spraying of the phosphating solution, and the first air drying time is 5min-8min; spray the phosphating solution for the second time on the extruded aluminum alloy that has completed the first air drying, and air dry for the second time after the second spraying of the phosphating solution, and the second air drying time is 10min-20min;

[0024] Step 12: Silanization treatment; immerse the extruded aluminum alloy that has completed the surface phosphating treatment in step 11 into the composite silane solution; the immersion time is 10s-15s, and after the immersion is completed, cure at 120℃-150℃ for 30min-35min.

[0025] Furthermore, the phosphating solution includes the following preparation raw materials:

[0026] Zn(H2PO4)2 5g / L-8g / L, Zn(NO3)2·6H20 8g / L-1 2g / L, Ni(NO3)2·6H2O 1g / L-3g / L, Mn(NO3)2 0.1g / L-0.4g / L, sodium fluorosilicate 0.4g / L-0.8g / L, tartaric acid 1g / L-2g / L, hydroxylamine hydrochloride 0.2g / L-0.4g / L, balance water.

[0027] Furthermore, the composite silane solution is prepared by the following steps:

[0028] A silane coupling agent, ethanol and deionized water are stirred and mixed in a weight ratio of 10:25:65, wherein the silane coupling agent is a mixture of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(methacryloyloxy)propyltrimethoxysilane in a weight ratio of 1:1; then gadolinium nitrate is added in an amount of 0.3 g / L, stirred and mixed, the pH is adjusted to 7, and hydrolyzed at room temperature for 2 hours to obtain a composite silane solution.

[0029] The above technical solution is made of the following components in mass percentage: Zn 6.1% to 6.4%, Mg 1.5% to 1.7%, Cu 0.25% to 0.35%, Fe ≤ 0.15%, Si ≤ 0.04%, Ti 0.03% to 0.08%, and the balance is Al; and by selecting Al-20Cu alloy, Al-5Ti-B alloy wire and aluminum ingots with a purity of 99.8%, zinc ingots with a purity of 99.9%, and magnesium ingots with a purity of 99.9% as raw materials; and by refining, ultrasonic treatment, refinement treatment, degassing filtration, ingot casting, and aging treatment, a 7 series aluminum alloy with fine grains, high strength, and good corrosion resistance is obtained, and its strength is not lower than the strength obtained by the peak aging process;

[0030] When the alloy is melted and cast, ultrasonic casting technology is used to treat the melt with ultrasonic waves. Through the "cavitation effect", the crystal nucleation is increased, the crystal grains are broken, the crystal grains are refined, and the comprehensive mechanical properties of the alloy are improved.

[0031] Through extrusion and heat treatment processes, a discontinuous coarse η phase is produced at the grain boundary through a regression and re-aging process, which delays the occurrence of corrosion along the grain boundary and improves the corrosion resistance of the alloy.

[0032] The 7 series high-strength corrosion-resistant aluminum alloy has a tensile strength greater than 580MPa, a yield strength greater than 550MPa, an elongation greater than 14%, and an exfoliation corrosion resistance grade not lower than PA grade. Its strength and corrosion resistance are balanced, and can meet the current needs of high strength and strong corrosion resistance in the field. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0035] A 7 series high-strength and corrosion-resistant aluminum alloy in one embodiment of the present invention includes the following components in mass percentage: Zn 6.1% to 6.4%, Mg 1.5% to 1.7%, Cu 0.25% to 0.35%, Fe ≤ 0.15%, Si ≤ 0.04%, Ti 0.03% to 0.08%, and the balance is Al.

[0036] In one of the embodiments, other impurities are also included, and the total amount of the other impurities is ≤0.15%.

[0037] In one of the embodiments, the 7 series high-strength corrosion-resistant aluminum alloy has a tensile strength greater than 580 MPa, a yield strength greater than 550 MPa, an elongation greater than 14%, and an exfoliation corrosion resistance grade not lower than PA grade.

[0038] The technical solution also provides a method for preparing a 7-series high-strength and corrosion-resistant aluminum alloy, comprising the following steps: Step 1: selecting Al-20Cu alloy, Al-5Ti-B alloy wire, aluminum ingots with a purity of 99.8%, zinc ingots with a purity of 99.9%, and magnesium ingots with a purity of 99.9% as raw materials;

[0039] Step 2: heating the aluminum ingot to melt at 730-750°C, then adding 6.1%-6.4% of zinc ingot, 1.5%-1.7% of magnesium ingot, and 1.25%-1.75% of Al-20Cu alloy accounting for the total weight of the raw materials, stirring and melting to form an aluminum alloy melt;

[0040] Step 3: Use sodium-free refining agent and argon gas to spray refine the aluminum alloy melt at a refining temperature of 730℃~750℃, and refine it multiple times. Each refining time is 25min~40min. After refining, slag is removed and then left to stand for 25min~35min.

[0041] Step 4: Use ultrasonic metal melt treatment equipment to ultrasonically treat the aluminum alloy melt, with a power of 150W to 200W and a vibration time of 5min to 10min;

[0042] Step 5: The aluminum alloy melt in the furnace is introduced into the flow channel, and the Al-5Ti-B alloy wire is added into the aluminum alloy melt for online grain refinement treatment;

[0043] Step 6: The aluminum alloy melt is sequentially passed through a degassing box with a rotation speed of 200 to 300 rpm and an argon flow rate of 4 to 5 cubic meters per hour and a double-layer foam ceramic filter plate with a porosity of 40ppi+60ppi, for online degassing and filtration treatment;

[0044] Step 7: semi-continuously casting the aluminum alloy melt into an aluminum alloy ingot under the conditions of a casting temperature of 710°C to 740°C, a casting speed of 90mm / min to 100mm / min, and a cooling water pressure of 0.1Mpa to 0.2Mpa;

[0045] Step 8: Heat the aluminum alloy ingot to 450℃~490℃ for homogenization treatment for 20-28 hours, and then force cool it to room temperature with water mist;

[0046] Step 9: heating the aluminum alloy ingot after homogenization treatment to 450°C to 470°C, extruding it at an extrusion speed of 8m / min to 12m / min to obtain an extruded aluminum alloy, and then cooling it to room temperature through water;

[0047] Step 10: Heat the extruded aluminum alloy to 110℃~130℃ and age for 22 hours to 26 hours, then quickly heat to 185℃-210℃ and keep warm for 15min-25min, quickly water cool to room temperature and continue to heat to 110℃~130℃ and age for 22 hours to 26 hours.

[0048] In one embodiment, in the third step, the amount of sodium-free refining agent added is calculated based on 3 kg of refining agent per ton of aluminum alloy melt.

[0049] In one embodiment, in the fifth step, the Al-5Ti-B alloy wire is added online at a rate of 0.004% to 0.01% of the total raw material addition amount, and the adding speed is 2m / min to 3m / min.

[0050] In one embodiment, in the ninth step, the extrusion die temperature is 440°C-460°C, the extrusion barrel temperature is 400°C-420°C, and the outlet temperature is 490°C-510°C.

[0051] In one embodiment, the preparation method of the 7 series high-strength corrosion-resistant aluminum alloy further includes the following steps:

[0052] Step 11: Surface phosphating treatment; cool the extruded aluminum alloy that has completed the aging treatment in step 10 to 60°C-80°C, degrease the surface of the extruded aluminum alloy after cooling, and wash and dry it with deionized water after degreasing; preheat the extruded aluminum alloy to 70°C-80°C; spray the phosphating solution for the first time after preheating; air dry for the first time after the first spraying of the phosphating solution, and the first air drying time is 5min-8min; spray the phosphating solution for the second time on the extruded aluminum alloy that has completed the first air drying, and air dry for the second time after the second spraying of the phosphating solution, and the second air drying time is 10min-20min;

[0053] Step 12: Silanization treatment; immerse the extruded aluminum alloy that has completed the surface phosphating treatment in step 11 into the composite silane solution; the immersion time is 10s-15s, and after the immersion is completed, cure at 120℃-150℃ for 30min-35min.

[0054] In one embodiment, the phosphating solution includes the following preparation raw materials:

[0055] Zn(H2PO4)2 5g / L-8g / L, Zn(NO3)2·6H20 8g / L-1 2g / L, Ni(NO3)2·6H2O 1g / L-3g / L, Mn(NO3)2 0.1g / L-0.4g / L, sodium fluorosilicate 0.4g / L-0.8g / L, tartaric acid 1g / L-2g / L, hydroxylamine hydrochloride 0.2g / L-0.4g / L, balance water.

[0056] In one embodiment, the composite silane solution is prepared by the following steps:

[0057] A silane coupling agent, ethanol and deionized water are stirred and mixed in a weight ratio of 10:25:65, wherein the silane coupling agent is a mixture of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(methacryloyloxy)propyltrimethoxysilane in a weight ratio of 1:1; then gadolinium nitrate is added in an amount of 0.3 g / L, stirred and mixed, the pH is adjusted to 7, and hydrolyzed at room temperature for 2 hours to obtain a composite silane solution.

[0058] In one embodiment, the refining times is 2 times.

[0059] The above technical solution is made of the following components in mass percentage: Zn 6.1% to 6.4%, Mg 1.5% to 1.7%, Cu 0.25% to 0.35%, Fe ≤ 0.15%, Si ≤ 0.04%, Ti 0.03% to 0.08%, and the balance is Al; and by selecting Al-20Cu alloy, Al-5Ti-B alloy wire and aluminum ingots with a purity of 99.8%, zinc ingots with a purity of 99.9%, and magnesium ingots with a purity of 99.9% as raw materials; and by refining, ultrasonic treatment, refinement treatment, degassing filtration, ingot casting, and aging treatment to obtain a 7 series aluminum alloy with fine grains, high strength, and good corrosion resistance, and its strength is not lower than the strength obtained by the peak aging process;

[0060] When the alloy is melted and cast, ultrasonic casting technology is used to treat the melt with ultrasonic waves. Through the "cavitation effect", the crystal nucleation is increased, the crystal grains are broken, the crystal grains are refined, and the comprehensive mechanical properties of the alloy are improved.

[0061] Through extrusion and heat treatment processes, a discontinuous coarse η phase is produced at the grain boundary through a regression and re-aging process, which delays the occurrence of corrosion along the grain boundary and improves the corrosion resistance of the alloy.

[0062] The 7 series high-strength corrosion-resistant aluminum alloy has a tensile strength greater than 580MPa, a yield strength greater than 550MPa, an elongation greater than 14%, and an exfoliation corrosion resistance grade not lower than PA grade. Its strength and corrosion resistance are balanced, and can meet the current needs of high strength and strong corrosion resistance in the field.

[0063] The embodiments of the present invention will be described in detail below with reference to specific examples.

[0064] Embodiment 1:

[0065] The aluminum alloy is composed of the following components in mass percentage: Zn 6.1%, Mg 1.7%, Cu 0.25%, Fe 0.12%, Si 0.034%, Ti 0.03%, and the balance is Al and other inevitable impurities. The individual content of other impurities is ≤ 0.05%; the total amount of other impurities is ≤ 0.15%. The preparation method includes the following steps:

[0066] Step 1: Select Al-20Cu alloy, Al-5Ti-B alloy wire, aluminum ingot with a purity of 99.8%, zinc ingot with a purity of 99.9%, and magnesium ingot with a purity of 99.9% as raw materials;

[0067] Step 2: Heat the aluminum ingot at 730°C to melt it, then add 6.1% of zinc ingot, 1.7% of magnesium ingot, and 1.25% of Al-20Cu alloy, which account for 6.1% of the total weight of the raw materials, and stir and melt them into an aluminum alloy melt;

[0068] Step 3: Use sodium-free refining agent and argon gas to spray and refine the aluminum alloy melt at a ratio of 3 kg refining agent / ton of aluminum alloy melt, the refining temperature is 730℃, and the refining is repeated twice, each time for 40 minutes. After slagging, let it stand for 25 minutes;

[0069] Step 4: Use ultrasonic metal melt treatment equipment to ultrasonically treat the aluminum alloy melt with a power of 150W and a vibration time of 10 minutes;

[0070] Step 5: The aluminum alloy melt in the furnace is introduced into the flow channel, and Al-5Ti-B alloy wire accounting for 0.004% of the total weight of the raw materials is added into the aluminum alloy melt for online grain refinement treatment at a speed of 2 m / min;

[0071] Step 6: The aluminum alloy liquid is sequentially passed through a degassing box with a rotation speed of 300 rpm and an argon flow rate of 5 cubic meters per hour and a double-layer foam ceramic filter plate with a porosity of 40ppi+60ppi, for online degassing and filtration treatment;

[0072] Step 7: semi-continuously casting the aluminum alloy liquid into an aluminum alloy ingot under the conditions of a casting temperature of 710°C, a casting speed of 90mm / min, and a cooling water pressure of 0.1Mpa;

[0073] Step 8: Heat the aluminum alloy ingot to 450°C for homogenization treatment for 28 hours, and then force cool it to room temperature with water mist;

[0074] Step 9: Heat the homogenized aluminum alloy ingot to 450°C, extrude it under the conditions of a mold temperature of 440°C, an extrusion barrel temperature of 400°C, an outlet temperature of 490°C, and an extrusion speed of 12m / min, and then cool it to room temperature through water;

[0075] Step 10: Heat the extruded aluminum alloy to 110°C and age for 26 hours, then quickly heat to 210°C and keep warm for 15 minutes, quickly water cool to room temperature and continue heating to 110°C and age for 26 hours.

[0076] Example 2

[0077] The aluminum alloy is composed of the following components in mass percentage: Zn 6.4%, Mg 1.5%, Cu 0.35%, Fe 0.09%, Si 0.029%, Ti 0.08%, and the balance is Al and other inevitable impurities. The content of other impurities is ≤ 0.05%; the total amount of other impurities is ≤ 0.15%. The preparation method includes the following steps:

[0078] Step 1: Select Al-20Cu alloy, Al-5Ti-B alloy wire, aluminum ingot with a purity of 99.8%, zinc ingot with a purity of 99.9%, and magnesium ingot with a purity of 99.9% as raw materials;

[0079] Step 2: Heat the aluminum ingot at 750°C to melt it, then add 6.4% of zinc ingot, 1.5% of magnesium ingot, and 1.75% of Al-20Cu alloy, which account for 6.4% of the total weight of the raw materials, and stir and melt them into an aluminum alloy melt;

[0080] Step 3: Use sodium-free refining agent and argon gas to spray and refine the aluminum alloy melt at a ratio of 3 kg refining agent / ton of aluminum alloy melt, the refining temperature is 750℃, and the refining is repeated twice, each time for 25 minutes. After slagging, let it stand for 35 minutes;

[0081] Step 4: Use ultrasonic metal melt treatment equipment to ultrasonically treat the aluminum alloy melt, with a power of 200W and a vibration time of 5 minutes;

[0082] Step 5: The aluminum alloy melt in the furnace is introduced into the flow channel, and Al-5Ti-B alloy wire accounting for 0.01% of the total weight of the raw materials is added into the aluminum alloy melt for online grain refinement treatment at a speed of 3 m / min;

[0083] Step 6: The aluminum alloy liquid is sequentially passed through a degassing box with a rotation speed of 200 rpm and an argon flow rate of 4 cubic meters per hour and a double-layer foam ceramic filter plate with a porosity of 40ppi+60ppi, for online degassing and filtration treatment;

[0084] Step 7: semi-continuously casting the aluminum alloy liquid into an aluminum alloy ingot under the conditions of a casting temperature of 740°C, a casting speed of 100mm / min, and a cooling water pressure of 0.2Mpa;

[0085] Step 8: Heat the aluminum alloy ingot to 490°C for homogenization treatment for 20 hours, and then force cool it to room temperature with water mist;

[0086] Step 9: Heat the homogenized aluminum alloy ingot to 470°C, extrude it under the conditions of mold temperature of 460°C, extrusion barrel temperature of 420°C, outlet temperature of 510°C, extrusion speed of 8m / min, and then cool it to room temperature through water;

[0087] Step 10: Heat the extruded aluminum alloy to 130°C for aging for 22 hours, then quickly heat to 185°C and keep warm for 25 minutes, quickly water cool to room temperature and continue heating to 130°C for aging for 22 hours.

[0088] Example 3

[0089] The aluminum alloy is composed of the following components in mass percentage: Zn 6.2%, Mg 1.6%, Cu 0.3%, Fe 0.1%, Si 0.026%, Ti 0.06%, and the balance is Al and other inevitable impurities. The content of other impurities is ≤ 0.05% each, and the total amount of other impurities is ≤ 0.15%. The preparation method includes the following steps:

[0090] Step 1: Select Al-20Cu alloy, Al-5Ti-B alloy wire, aluminum ingot with a purity of 99.8%, zinc ingot with a purity of 99.9%, and magnesium ingot with a purity of 99.9% as raw materials;

[0091] Step 2: Heat the aluminum ingot at 740°C to melt it, then add 6.2% of the total weight of the raw materials, 1.6% of the magnesium ingot, and 1.5% of the Al-20Cu alloy, and stir and melt them into an aluminum alloy melt;

[0092] Step 3: Use sodium-free refining agent and argon gas to spray and refine the aluminum alloy melt at a ratio of 3 kg refining agent / ton of aluminum alloy melt, the refining temperature is 740℃, and the refining is repeated twice, each time for 30 minutes. After slagging, let it stand for 30 minutes;

[0093] Step 4: Use ultrasonic metal melt treatment equipment to ultrasonically treat the aluminum alloy melt with a power of 170W and a vibration time of 8 minutes;

[0094] Step 5: The aluminum alloy melt in the furnace is introduced into the flow channel, and Al-5Ti-B alloy wire accounting for 0.007% of the total weight of the raw materials is added into the aluminum alloy melt for online grain refinement treatment at a speed of 2.5 m / min;

[0095] Step 6: The aluminum alloy liquid is sequentially passed through a degassing box with a rotation speed of 250 rpm and an argon flow rate of 4.5 cubic meters per hour and a double-layer foam ceramic filter plate with a porosity of 40ppi+60ppi, for online degassing and filtration treatment;

[0096] Step 7: semi-continuously casting the aluminum alloy liquid into an aluminum alloy ingot under the conditions of a casting temperature of 720°C, a casting speed of 95mm / min, and a cooling water pressure of 0.15Mpa;

[0097] Step 8: Heat the aluminum alloy ingot to 460°C for homogenization treatment for 24 hours, and then force cool it to room temperature with water mist;

[0098] Step 9: Heat the homogenized aluminum alloy ingot to 460°C, extrude it under the conditions of a mold temperature of 450°C, an extrusion barrel temperature of 410°C, an outlet temperature of 500°C, and an extrusion speed of 10m / min, and then cool it to room temperature through water;

[0099] Step 10: Heat the extruded aluminum alloy to 120°C for aging for 24 hours, then quickly heat to 200°C and keep warm for 20 minutes, quickly water cool to room temperature and continue heating to 120°C for aging for 24 hours.

[0100] Example 4

[0101] On the basis of Example 3, the following process is added;

[0102] Step 11: Surface phosphating treatment; cool the extruded aluminum alloy that has completed the aging treatment in step 10 to 70°C, degrease the surface of the extruded aluminum alloy after cooling, and wash and dry it with deionized water after degreasing; preheat the extruded aluminum alloy to 75°C; spray the phosphating solution for the first time after preheating; air dry for the first time after the first spraying of the phosphating solution, and the first air drying time is 6 minutes; spray the phosphating solution for the second time on the extruded aluminum alloy that has completed the first air drying, and air dry for the second time after the second spraying of the phosphating solution, and the second air drying time is 15 minutes;

[0103] Step 12: Silanization treatment; immerse the extruded aluminum alloy that has completed the surface phosphating treatment in step 11 into the composite silane solution; the immersion time is 15 seconds, and after the immersion is completed, it is cured at 130°C for 30 minutes.

[0104] The phosphating solution comprises the following preparation raw materials:

[0105] Zn(H2PO4)2 6g / L, Zn(NO3)2·6H20 10g / L, Ni(NO3)2·6H2O 2g / L, Mn(NO3)2 0.2g / L, sodium fluorosilicate 0.6g / L, tartaric acid 1g / L, hydroxylamine hydrochloride 0.3g / L, balance water.

[0106] The composite silane solution comprises the following steps:

[0107] A silane coupling agent, ethanol and deionized water are stirred and mixed in a weight ratio of 10:25:65, wherein the silane coupling agent is a mixture of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(methacryloyloxy)propyltrimethoxysilane in a weight ratio of 1:1; then gadolinium nitrate is added in an amount of 0.3 g / L, stirred and mixed, the pH is adjusted to 7, and hydrolyzed at room temperature for 2 hours to obtain a composite silane solution.

[0108] The degreasing is carried out by spraying, and the degreasing agent is made of the following raw materials in parts by weight: 8 parts of sodium hydroxide, 18 parts of triethanolamine, 2 parts of dodecyl alcohol amide phosphate, 1.5 parts of sodium methylene bismethylbenzene sulfonate, 0.7 parts of sodium carboxymethyl cellulose, 3 parts of ethanol, 1.5 parts of sodium tripolyphosphate, and 66 parts of deionized water.

[0109] Comparative Example 1

[0110] The aluminum alloy is composed of the following components in mass percentage: Zn 5.6%, Mg 1.6%, Cu 0.28%, Fe 0.2%, Si 0.08%, Ti 0.05%, and the balance is Al and unavoidable impurities. The individual content of other impurities is ≤ 0.05%; the total amount of other impurities is ≤ 0.15%. The preparation method includes the following steps:

[0111] Step 1: Select Al-20Cu alloy, Al-5Ti-B alloy wire and aluminum ingot, zinc ingot and magnesium ingot as raw materials;

[0112] Step 2: Heat the aluminum ingot at 730°C to melt it, then add 5.6% of zinc ingot, 1.6% of magnesium ingot, and 1.4% of Al-20Cu alloy, which account for 5.6% of the total weight of the raw materials, and stir and melt them into an aluminum alloy melt;

[0113] Step 3: Use sodium-free refining agent and argon gas to spray and refine the aluminum alloy melt at a ratio of 3 kg refining agent / ton of aluminum alloy melt, the refining temperature is 740℃, and the refining is repeated twice, each time for 30 minutes. After slagging, let it stand for 30 minutes;

[0114] Step 4: Use ultrasonic metal melt treatment equipment to ultrasonically treat the aluminum alloy melt with a power of 170W and a vibration time of 8 minutes;

[0115] Step 5: The aluminum alloy melt in the furnace is introduced into the flow channel, and Al-5Ti-B alloy wire accounting for 0.006% of the total weight of the raw materials is added into the aluminum alloy melt for online grain refinement treatment at a speed of 2.5 m / min;

[0116] Step 6: The aluminum alloy liquid is sequentially passed through a degassing box with a rotation speed of 250 rpm and an argon flow rate of 4.5 cubic meters per hour and a double-layer foam ceramic filter plate with a porosity of 40ppi+60ppi, for online degassing and filtration treatment;

[0117] Step 7: semi-continuously casting the aluminum alloy liquid into an aluminum alloy ingot under the conditions of a casting temperature of 720°C, a casting speed of 95mm / min, and a cooling water pressure of 0.15Mpa;

[0118] Step 8: Heat the aluminum alloy ingot to 460°C for homogenization treatment for 24 hours, and then force cool it to room temperature with water mist;

[0119] Step 9: Heat the homogenized aluminum alloy ingot to 460°C, extrude it under the conditions of a mold temperature of 450°C, an extrusion barrel temperature of 410°C, an outlet temperature of 500°C, and an extrusion speed of 10m / min, and then cool it to room temperature through water;

[0120] Step 10: Heat the extruded aluminum alloy to 120°C for aging for 24 hours, then quickly heat to 200°C and keep warm for 20 minutes, quickly water cool to room temperature and continue heating to 120°C for aging for 24 hours.

[0121] Comparative Example 2

[0122] The difference between Comparative Example 2 and Example 3 is that the fourth step is not performed, that is, the refined melt is not subjected to ultrasonic treatment, and the fifth step is directly performed.

[0123] Comparative Example 3

[0124] The difference between Comparative Example 3 and Example 3 is that the tenth step is to subject the aluminum alloy profile after quenching to a single-stage aging heat treatment, the aging temperature is 120° C., the insulation time is 24 h, and finally the aluminum alloy profile after aging heat treatment is air-cooled to room temperature.

[0125] Comparative Example 4

[0126] The difference between Comparative Example 4 and Example 3 is that the tenth step is to subject the quenched aluminum alloy profile to a double-stage aging heat treatment, wherein the first-stage aging temperature is 105°C, the holding time is 8 hours, the second-stage aging temperature is 150°C, the holding time is 8 hours, and finally the aluminum alloy profile after the aging heat treatment is air-cooled to room temperature.

[0127] Comparative Example 5

[0128] The difference from Example 3 is that the aluminum alloy is composed of the following components in mass percentage: Zn 5.9%, Mg 1.4%, Cu 0.2%, Fe 0.1%, Si 0.026%, Ti 0.06%, and the balance is Al and other inevitable impurities. The content of each other impurity is ≤ 0.05%; the total amount of impurities is ≤ 0.15%.

[0129] Step 2: Heat the aluminum ingot at 740°C to melt it, then add 5.9% of the total weight of the raw materials, 1.4% of the magnesium ingot, and 1% of the Al-20Cu alloy, and stir and melt them into an aluminum alloy melt.

[0130] The other preparation processes are the same as those in Example 3.

[0131] Comparative Example 6

[0132] The difference from Example 3 is that the aluminum alloy consists of the following components in mass percentage: Zn 6.5%,

[0133] Mg1.8%, Cu0.36%, Fe0.1%, Si0.026%, Ti0.06%, the balance is Al and other unavoidable impurities. The content of other impurities is ≤0.05%; the total amount of impurities is ≤0.15%.

[0134] Step 2: Heat the aluminum ingot at 740°C to melt it, then add 6.5% of zinc ingot, 1.8% of magnesium ingot, and 1.8% of Al-20Cu alloy, which account for 6.5% of the total weight of the raw materials, and stir and melt them into an aluminum alloy melt.

[0135] The other preparation processes are the same as those in Example 3.

[0136] Comparative Example 7

[0137] The preparation process is the same as that of Example 4, but the silanization treatment in the twelfth step is not performed.

[0138] Comparative Example 8

[0139] The preparation process is the same as that of Example 4, but the surface phosphating treatment in the eleventh step is not performed.

[0140] Comparative Example 9

[0141] The preparation process is the same as that of Comparative Example 2, and the surface phosphating treatment in the eleventh step and the silanization treatment in the twelfth step of Example 4 are added.

[0142] Comparative Example 10

[0143] The preparation process is the same as that of Comparative Example 4, and the surface phosphating treatment in the eleventh step and the silanization treatment in the twelfth step of Example 4 are added.

[0144] Comparative Example 11

[0145] The preparation process is the same as that of Example 4, but the steps for preparing the composite silane solution are changed to:

[0146] A silane coupling agent, ethanol and deionized water were stirred and mixed in a weight ratio of 10:25:65, wherein the silane coupling agent was a mixture of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(methacryloyloxy)propyltrimethoxysilane in a weight ratio of 1:1; the pH was adjusted to 7 and hydrolyzed at room temperature for 2 hours.

[0147] The aluminum alloys prepared in Examples 1-4 and Comparative Examples 1-11 were subjected to relevant performance tests, and the results are shown in Table 1. The mechanical properties of the products were tested in accordance with GB / T228.1-2010 "Tensile Tests for Metallic Materials Part 1: Room Temperature Test Methods"; the products were subjected to a 48-hour exfoliation corrosion test in accordance with ASTMG34-01 "Standard Test Method for Exfoliation CorrosionSusceptibility in 2XXX and 7XXX Series Aluminum Alloys", and the salt spray resistance was tested in a salt spray test chamber in accordance with GB / T 2423.17.2008 / IEC60068-2-11:1981 "Environmental Testing for Electrical and Electronic Products - Salt Spray".

[0148] Table 1:

[0149]

[0150]

[0151] “-” means not testing the item;

[0152] The difference between Examples 1-3 is that the raw material addition amount of the aluminum alloy is different. As shown in Table 1, the aluminum alloy prepared in Examples 1-3 has a tensile strength greater than 580 MPa, a yield strength greater than 550 MPa, an elongation greater than 14%, and an anti-scaling corrosion grade not lower than PA grade. Its strength and corrosion resistance are balanced, which can meet the current demand for high strength and strong corrosion resistance.

[0153] The difference between Comparative Example 1 and Example 3 is that the Zn content in the added raw materials is less than 6.1%, and the Fe content is 0.2% and the Si content is 0.08%. When the Fe and Si contents are high, the strength performance and anti-exfoliation corrosion performance of the prepared aluminum alloy are more affected. Controlling the Fe and Si contents at lower levels has a greater positive effect on achieving high-strength and corrosion-resistant aluminum alloys. Fe and Si are unavoidable harmful impurities in 7 series aluminum alloys. These impurities mainly exist in the form of hard and brittle FeAl3 and free Si, among which FeAl3 has a greater effect on corrosion resistance. These insoluble second phases often act as notches, easily becoming crack sources that cause the material to break, which is detrimental to the strength and plasticity of the aluminum alloy. Therefore, it is necessary to strictly control the content of Fe and Si. The present invention selects aluminum ingots with a purity of ≥99.8%, zinc ingots with a purity of ≥99.9%, and magnesium ingots with a purity of ≥99.9% as raw materials, controls the content of Fe to less than 0.15%, and the content of Si to less than 0.04%, and combines the subsequent ingot homogenization treatment to eliminate the negative effects of Fe and Si impurity elements.

[0154] The difference between Comparative Example 2 and Example 3 is that ultrasonic treatment is not performed. It can be seen from the data in Table 1 that compared with Example 3, the tensile strength, yield strength and elongation of Comparative Example 2 are all reduced, and the performance effect of the aluminum alloy prepared in Example 3, that is, the tensile strength is greater than 580 MPa, the yield strength is greater than 550 MPa, and the elongation is greater than 14%; the use of ultrasonic treatment can improve the strength performance of the aluminum alloy, so when the alloy is melted and cast, ultrasonic casting technology is used to perform ultrasonic treatment on the melt at the optimal frequency, and the "cavitation effect" is used to increase the nucleation of grains and break the grains, thereby achieving grain refinement and improving the comprehensive mechanical properties of the alloy.

[0155] The difference between Comparative Example 3 and Example 3 is that Comparative Example 3 adopts single-stage aging treatment. It can be seen from the data in Table 1 that compared with Example 3, the exfoliation corrosion level of Comparative Example 3 is not as good as the exfoliation corrosion level of Example 3. In the present invention, a discontinuous coarse η phase is generated at the grain boundary through an extrusion process and a heat treatment process, and a regression and re-aging process, which delays the occurrence of corrosion along the grain boundary and improves the corrosion resistance of the alloy.

[0156] The difference between Comparative Example 4 and Example 3 is that Comparative Example 4 adopts different aging temperatures and holding times. It can be seen from the data in Table 1 that compared with Example 3, the exfoliation corrosion grade of Comparative Example 4 is not as good as that of Example 3, and the degree of excellence of the exfoliation corrosion grade decreases in order from Example 3 to Comparative Example 4 and Comparative Example 3. It can be seen that the regression and re-aging process can significantly improve the corrosion resistance of the aluminum alloy compared with the single-stage aging heat treatment. At the same time, the optimal corrosion resistance is achieved in the treatment process of aging at 110°C to 130°C for 22 hours to 26 hours, then rapidly heating to 185°C-210°C for 15 minutes to 25 minutes, rapidly cooling to room temperature, and then continuing to heat to 110°C to 130°C for 22 hours to 26 hours. The applicant has found through the study of the aging process of the aluminum alloy of the present invention that the first 120℃×24h pre-aging can ensure that fine and dispersed GP zones and η′ phases are precipitated from the solid solution to a large extent, and then a short-time high-temperature regression treatment of 200℃×20min is performed, and the GP zones smaller than the critical size are dissolved into the matrix again, and a part of the GP zones larger than the critical size will be retained, and the other part will be converted into a metastable η′ phase or an equilibrium phase η phase. Finally, 120℃×24h re-aging is performed, and the fine η′ phase is re-precipitated. Combined with the alloy composition design, the alloy strength is ultimately higher than the single-stage peak aging. At the same time, through the above-mentioned aging system, there are discontinuous coarse η phases at the grain boundaries. Such grain boundary morphology is not easy to form a continuous corrosion channel, which can delay the occurrence of corrosion along the grain boundary. Combined with the alloy composition design, the corrosion resistance of the alloy is stronger than that of the double-stage aging. If the aging process parameters are not within the above-mentioned matching range, the expected aluminum alloy strength and corrosion resistance cannot be achieved.

[0157] The difference between Comparative Example 5 and Example 3 is that the amount of raw material added is different, wherein the Zn content is 5.9%, the Mg content is 1.4%, and the Cu content is 0.2%. It can be seen from Table 1 that the tensile strength, yield strength, and elongation of Comparative Example 5 are lower than those of Example 3. Combining Examples 1-3, it can be seen that when the Zn content is less than 6.1%, the Mg content is less than 1.5%, and the Cu content is less than 0.25%, the tensile strength and yield strength of the aluminum alloy cannot reach 580MPa and 550Mpa, respectively;

[0158] The difference between Comparative Example 6 and Example 3 is that the addition amount of raw materials is different, wherein the Zn content is 6.5%, the Mg content is 1.8%, and the Cu content is 0.36%. From the data in Table 1, it can be seen that the tensile strength, yield strength, and elongation of Comparative Example 6 are lower than those of Example 3. At the same time, combined with Examples 1-3, it can be seen that when the Zn content is greater than 6.4%, the Mg content is greater than 1.7%, and the Cu content is greater than 0.35%, the plasticity and corrosion resistance of the alloy will be significantly deteriorated. Only when the Zn content is 6.1-6.4%, the Mg content is 1.5-1.7%, and the Cu content is 0.25-0.35%, can the aluminum alloy obtain high strength and high corrosion resistance.

[0159] Example 4 adds the surface phosphating treatment of the eleventh step and the silanization treatment of the twelfth step on the basis of Example 3; it can be seen from the comparison between Example 3 and Example 4 that the salt spray resistance test performance of Example 4 is better than that of Example 3, and it can be seen that the salt spray resistance of the aluminum alloy can be improved after the surface phosphating treatment and silanization treatment, thereby improving the overall corrosion resistance of the aluminum alloy. After the extruded aluminum alloy is cooled to 60℃-80℃, it is degreased, and the residual heat of the extruded aluminum alloy after the aging treatment is used for degreasing, which saves energy and ensures the continuity of the process. Multiple coatings of phosphating liquid can make the phosphating treatment effect of the aluminum alloy surface better, and the residual heat sprays the phosphating liquid and air-dries. This process can quickly perform phosphating and reduce the time required for production; at the same time, after the surface phosphating treatment is completed, the silanization treatment is performed by immersion. This kind of construction and coating process is simple and easy to operate, so that the silanization treatment of the aluminum alloy surface is more uniform, and it is cured at 120℃-150℃ to quickly complete the silanization treatment of the aluminum alloy surface.

[0160] The difference between Comparative Example 7 and Example 4 is that Comparative Example 7 does not perform the twelfth step of silanization treatment. It can be seen from the data in Table 1 that the salt spray resistance of the aluminum alloy of Example 4 is better than the salt spray resistance of the aluminum alloy whose surface treatment is only surface phosphating treatment. It can be seen that the salt spray resistance of the aluminum alloy can be improved by combining the eleventh step of surface phosphating treatment with the twelfth step of silanization treatment, thereby improving the overall corrosion resistance of the aluminum alloy.

[0161] The difference between Comparative Example 8 and Example 4 is that Comparative Example 8 does not perform the eleventh step of surface phosphating treatment. It can be seen from the data in Table 1 that the salt spray resistance of the aluminum alloy of Example 4 is better than the salt spray resistance of the aluminum alloy whose surface treatment is only silanization treatment. It can be seen that the combination of the eleventh step of surface phosphating treatment and the twelfth step of silanization treatment can improve the salt spray resistance of the aluminum alloy, thereby improving the overall corrosion resistance of the aluminum alloy.

[0162] The difference between Comparative Example 9 and Comparative Example 2 is that Comparative Example 9 adds the surface phosphating treatment of the eleventh step and the silanization treatment of the twelfth step of Example 4. It can be seen from the data in Table 1 that the salt spray resistance of Comparative Example 9 subjected to the surface phosphating treatment and the silanization treatment is better than that of Comparative Example 2. Therefore, the combination of surface phosphating treatment and silanization treatment can improve the salt spray resistance of the aluminum alloy, thereby improving the overall corrosion resistance of the aluminum alloy.

[0163] The difference between Comparative Example 10 and Comparative Example 4 is that Comparative Example 10 adds the surface phosphating treatment of the eleventh step and the silanization treatment of the twelfth step of Example 4. It can be seen from the data in Table 1 that the salt spray resistance of Comparative Example 4 is poor under the low-temperature double-stage aging, but after the process added in Comparative Example 10, the salt spray resistance of the aluminum alloy is significantly improved. Therefore, the combination of surface phosphating treatment and silanization treatment can improve the salt spray resistance of the aluminum alloy, thereby improving the overall corrosion resistance of the aluminum alloy.

[0164] The difference between Comparative Example 11 and Example 4 is that gadolinium nitrate is not added in the silanization process of Comparative Example 11. It can be seen from the data in Table 1 that Example 4 with added gadolinium nitrate has better salt spray resistance than Comparative Example 11 without adding gadolinium nitrate. It can be seen that adding gadolinium nitrate can improve the salt spray resistance of aluminum alloy, thereby improving the overall corrosion resistance of aluminum alloy.

[0165] In the present invention, Zn, Mg, and Cu are the main alloying elements of this series of aluminum alloys. In addition to improving the alloy strength through solid solution strengthening, the size and quantity of precipitation strengthening phases MgZn2 and CuAl2 can be changed through a heat treatment process to achieve a precipitation strengthening effect. Among them, the solubility of MgZn2 in Al is very large, and changes dramatically with the rise and fall of temperature, and has a very strong aging strengthening effect. The increase of Zn and Mg content can greatly improve the strength and hardness of the aluminum alloy, but the plasticity and corrosion resistance are reduced. Adding Cu element in an appropriate amount can also improve the supersaturation degree of the alloy, expand the stable temperature range of the GP zone, and improve tensile strength and plasticity, but the addition of Cu element has a tendency to produce pitting corrosion and should be controlled. Through systematic research on alloy components, the present invention finds that when the Zn content is less than 6.1%, the Mg content is less than 1.5%, and the Cu content is less than 0.25%, the tensile strength and yield strength of the aluminum alloy cannot reach 580MPa and 550Mpa respectively, and when the Zn content is greater than 6.4%, the Mg content is greater than 1.7%, and the Cu content is greater than 0.35%, the plasticity and corrosion resistance of the alloy will be significantly deteriorated. Only when the Zn content is 6.1-6.4%, the Mg content is 1.5%-1.7%, and the Cu content is 0.25%-0.35%, the aluminum alloy can obtain high strength and high corrosion resistance.

[0166] Ti is added through Al-5Ti-B wire modifier, which can refine the grains of aluminum alloy ingots and increase the recrystallization temperature. The Ti content is controlled at 0.03% to 0.08%, and combined with ultrasonic casting and other technologies, the grain size of the ingot can be controlled at 100 microns to 150 microns.

[0167] Improving the purity of aluminum alloy is the basis for ensuring that aluminum alloy obtains high comprehensive performance. The present invention first blows argon gas with sodium-free refining agent into the melt to mix, degas and remove impurities from the melt, and then flows the melt through a degassing box and a double-layer foam ceramic filter plate with a porosity of 40ppi+60ppi in sequence to deeply purify the melt and reduce the influence of pores and inclusions on the mechanical properties and corrosion resistance of aluminum alloy.

[0168] The grain refinement of the ingot is achieved by adding Al-5Ti-B wire modifier and ultrasonic treatment. When ultrasonic waves penetrate the melt, certain cavitation areas are formed inside the melt. These areas will form a large number of cavitation bubbles and absorb heat from the nearby melt, resulting in a large amount of local supercooling of the melt and increased nucleation, thereby achieving grain refinement. On the other hand, the local high temperature and high pressure generated by the unstable bubble crushing can also cause secondary grain crushing and refinement. The present invention is combined with Al-5Ti-B wire modifier, controls the ultrasonic power to 150W to 200W, and the vibration time to 5min-10min, and the casting grain size that can be obtained is 100 microns to 150 microns.

[0169] Homogenization treatment can improve the element segregation inside the alloy, improve the composition uniformity and extrudability, and have a certain effect on improving the final mechanical properties of the alloy. After a large number of experimental studies, the inventors of this case found that the ideal homogenization temperature and time of the aluminum alloy of the present invention are 450℃~490℃ and 20 hours-28 hours, which can completely eliminate the macro-micro segregation of elements inside the ingot and fully dissolve the elements and coarse intermetallic compounds.

[0170] Extrusion temperature, extrusion speed and quenching effect affect the supersaturated solid solubility of aluminum alloy, thus significantly affecting its final mechanical properties. The applicant has found through research on the extrusion process of the aluminum alloy of the present invention that heating the aluminum alloy ingot after homogenization treatment to 450℃~470℃, extruding under the conditions of mold temperature of 440℃-460℃, extrusion barrel temperature of 400℃-420℃, outlet temperature of 490℃-510℃, extrusion speed of 8m / min~12m / min, and then cooling to room temperature through water can ensure that the alloy has sufficient supersaturated solid solubility. If the outlet temperature is lower than 490℃, the excess phase in the alloy cannot be fully dissolved into the aluminum matrix. If the outlet temperature is higher than 510℃, it is easy to cause product surface quality problems.

[0171] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0172] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a 7 series high-strength corrosion-resistant aluminum alloy, characterized in that: The following steps are involved: Step 1: Select Al-20Cu alloy, Al-5Ti-B alloy wire, aluminum ingot with a purity of 99.8%, zinc ingot with a purity of 99.9%, and magnesium ingot with a purity of 99.9% as raw materials; Step 2: heating the aluminum ingot to melt at 730°C to 750°C, then adding 6.1% to 6.4% of zinc ingot, 1.5% to 1.7% of magnesium ingot, and 1.25% to 1.75% of Al-20Cu alloy accounting for the total weight of the raw materials, stirring and melting to form an aluminum alloy melt; Step 3: Use sodium-free refining agent and argon gas to spray refine the aluminum alloy melt at a refining temperature of 730℃~750℃, and refine it multiple times. Each refining time is 25min~40min. After refining, slag is removed and then left to stand for 25min~35min. Step 4: Use ultrasonic metal melt treatment equipment to ultrasonically treat the aluminum alloy melt, with a power of 150W to 200W and a vibration time of 5min to 10min; Step 5: The aluminum alloy melt in the furnace is introduced into the flow channel, and the Al-5Ti-B alloy wire is added into the aluminum alloy melt for online grain refinement treatment; Step 6: The aluminum alloy melt is sequentially passed through a degassing box with a rotation speed of 200 to 300 rpm and an argon flow rate of 4 to 5 cubic meters per hour and a double-layer foam ceramic filter plate with a porosity of 40ppi+60ppi, for online degassing and filtration treatment; Step 7: semi-continuously casting the aluminum alloy melt into an aluminum alloy ingot under the conditions of a casting temperature of 710°C to 740°C, a casting speed of 90mm / min to 100mm / min, and a cooling water pressure of 0.1Mpa to 0.2Mpa; Step 8: Heat the aluminum alloy ingot to 450°C to 490°C for homogenization treatment for 20 hours to 28 hours, and then force cool it to room temperature with water mist; Step 9: heating the aluminum alloy ingot after homogenization treatment to 450°C to 470°C, extruding it at an extrusion speed of 8m / min to 12m / min to obtain an extruded aluminum alloy, and then cooling it to room temperature through water; Step 10: Heat the extruded aluminum alloy to 110°C-130°C for aging for 22 hours-26 hours, then quickly heat to 185°C-210°C for 15 minutes-25 minutes, quickly cool to room temperature with water, and then continue to heat to 110°C-130°C for aging for 22 hours-26 hours; In the third step, the amount of sodium-free refining agent added is calculated based on 3 kg of refining agent per ton of aluminum alloy melt; The 7 series high-strength corrosion-resistant aluminum alloy is composed of the following components in mass percentage: Zn 6.1% to 6.4%, Mg 1.5% to 1.7%, Cu 0.25% to 0.35%, Fe≤0.15%, Si≤0.04%, Ti 0.03% to 0.08%, the total amount of other impurities ≤0.15%, and the balance is Al.

2. The method for preparing the 7 series high-strength corrosion-resistant aluminum alloy according to claim 1, characterized in that: In the fifth step, the Al-5Ti-B alloy wire is added online at a rate of 0.004% to 0.01% of the total raw material addition amount, and the adding speed is 2m / min to 3m / min.

3. The method for preparing the 7 series high-strength corrosion-resistant aluminum alloy according to claim 1, characterized in that: In the ninth step, the extrusion die temperature is 440°C-460°C, the extrusion barrel temperature is 400°C-420°C, and the outlet temperature is 490°C-510°C.

4. The method for preparing the 7 series high-strength corrosion-resistant aluminum alloy according to claim 1, characterized in that: The preparation method of the 7 series high-strength corrosion-resistant aluminum alloy further comprises the following steps: Step 11: Surface phosphating treatment; cool the extruded aluminum alloy that has completed the aging treatment in step 10 to 60°C-80°C, degrease the surface of the extruded aluminum alloy after cooling, and wash and dry it with deionized water after degreasing; preheat the extruded aluminum alloy to 70°C-80°C; spray the phosphating solution for the first time after preheating; air dry for the first time after the first spraying of the phosphating solution, and the first air drying time is 5min-8min; spray the phosphating solution for the second time on the extruded aluminum alloy that has completed the first air drying, and air dry for the second time after the second spraying of the phosphating solution, and the second air drying time is 10min-20min; Step 12: Silanization treatment; immerse the extruded aluminum alloy that has completed the surface phosphating treatment in step 11 into the composite silane solution; the immersion time is 10s-15s, and after the immersion is completed, cure at 120℃-150℃ for 30min-35min.

5. The method for preparing the 7 series high-strength corrosion-resistant aluminum alloy according to claim 4, characterized in that: The phosphating solution is obtained by preparing the following raw materials: Zn(H2PO4)2 5g / L-8g / L, Zn(NO3)2·6H20 8g / L-1 2g / L, Ni(NO3)2·6H2O1g / L-3g / L, Mn(NO3)2 0.1g / L-0.4g / L, sodium fluorosilicate 0.4g / L-0.8g / L, tartaric acid 1g / L-2g / L, hydroxylamine hydrochloride 0.2g / L-0.4g / L and the balance water.

6. The method for preparing the 7 series high strength and corrosion resistant aluminum alloy according to claim 4, characterized in that: The composite silane solution comprises the following steps: A silane coupling agent, ethanol and deionized water are stirred and mixed in a weight ratio of 10:25:65, wherein the silane coupling agent is a mixture of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(methacryloyloxy)propyltrimethoxysilane in a weight ratio of 1:1; then gadolinium nitrate is added in an amount of 0.3 g / L, stirred and mixed, the pH is adjusted to 7, and hydrolyzed at room temperature for 2 hours to obtain a composite silane solution.

Citation Information

Patent Citations

  • High-Zn, high-Mg and low-Cu ultrahigh-strength corrosion-resisting aluminum alloy and heat treatment method

    CN103014459A

  • High strength and toughness and high corrosion resistance aluminum alloy for automobile and preparation method of aluminum alloy

    CN107447142A

  • High-strength deformation Al-Zn-Mg-Cu alloy and preparation method thereof

    CN115505805A

  • High-strength corrosion-resistant lead-free free-cutting aluminum alloy and preparation method thereof

    CN115896557A

  • Method for casting a composite aluminium alloy ingot or billet

    WO2009024601A1